2019
DOI: 10.1177/1460408619886211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NSAID use on bone healing: A meta-analysis of retrospective case–control and cohort studies within clinical settings

Abstract: Introduction This meta-analysis aims to determine whether non-steroidal anti-inflammatory drug (NSAID) use is significantly associated with adverse bone healing outcomes within clinical settings, including trauma and elective spine settings. It will also explore bone healing outcomes with the type, route, dosage and duration of NSAID exposure and aims to demonstrate the effects of various other confounding factors on bone healing outcomes. Methods Electronic databases including MedLine, Embase and Cochrane wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…This may be due to the fact that pain management protocols do not automatically include NSAIDs and that clinicians may be reluctant to use them considering their effects on bone healing and the risk of bleeding after an injury. [84][85][86] As for cannabis, although most participants smoked it for recreational purposes, several also recognized its properties for pain relief and the improvement of associated symptoms. Previous studies have shown a marked interest (> 70%) in medical cannabis for patients after musculoskeletal injuries and orthopaedic procedures.…”
Section: Dovepressmentioning
confidence: 99%
“…This may be due to the fact that pain management protocols do not automatically include NSAIDs and that clinicians may be reluctant to use them considering their effects on bone healing and the risk of bleeding after an injury. [84][85][86] As for cannabis, although most participants smoked it for recreational purposes, several also recognized its properties for pain relief and the improvement of associated symptoms. Previous studies have shown a marked interest (> 70%) in medical cannabis for patients after musculoskeletal injuries and orthopaedic procedures.…”
Section: Dovepressmentioning
confidence: 99%
“…A 2020 meta-analysis (11 retrospective cohort studies, n=12,962; single prospective double-blind randomized controlled trial [RCT], n=98; single prospective cohort within a RCT, n=190; single retrospective case-control, n=377; single case-control, n=2,815) explored if the use of NSAIDs during the bone healing process is associated with an increased risk of bone healing complications. 1 Observational studies and RCTs on long bone fractures and spinal fusion, which assessed the effects of perioperative NSAID exposure on bone healing outcomes in all ages and sexes, were included. In vitro and animal studies were excluded along with review articles and studies with undefined methodology and/or insufficient data for analysis.…”
mentioning
confidence: 99%